Artemisinin therapy for malaria in hemoglobinopathies: A systematic review - Sugiarto, S.; Moore, Brioni; Makani, J.; Davis, T. (Oxford University Press, 2018)
© The Author(s) 2018. Artemisinin derivatives are widely used antimalarial drugs. There is some evidence from in vitro, animal and clinical studies that hemoglobinopathies may alter their disposition and antimalarial activity. This review assesses relevant data in a-thalassemia, sickle cell disease (SCD), ß-thalassemia and hemoglobin E. There is no convincing evidence that the disposition of artemisinin drugs is affected by hemoglobinopathies. Although in vitro studies indicate that Plasmodium falciparum cultured in thalassemic erythrocytes is relatively resistant to the artemisinin derivatives, mean 50% inhibitory concentrations (IC50s) are much lower than in vivo plasma concentrations after recommended treatment doses. Since IC50s are not increased in P. falciparum cultures using SCD erythrocytes, delayed post-treatment parasite clearance in SCD may reflect hyposplenism. As there have been no clinical studies suggesting that hemoglobinopathies significantly attenuate the efficacy of artemisinin combination therapy (ACT) in uncomplicated malaria, recommended artemisinin doses as part of ACT remain appropriate in this patient group.